A Legal Analysis of the Management of the Lewu Tehang Indigenous Territory and Indigenous Forest as Set Forth in the Dayak Ngaju Lewu Tehang Customary Law - Yosefa Sefta; Rico Septian Noor; Yacob F. Martono; Rizki Setyobowo Sangalang (Journal Research of Social Science, Economics, and Management, 2026)
This article analyzes the juridical management of the customary territory and customary forest of Lewu Tehang within the framework of the customary law of the Dayak Ngaju Lewu Tehang. This research was researched with empirical juridical and normative juridical research methods aimed at uncovering the alignment between the norms of Dayak customary law ngaju lewu tehang and national regulations, including the recognition of indigenous peoples' rights to customary forests. Based on Article 18B paragraph (2) of the 1945 Constitution: the Indonesian state recognizes and respects the unity and unity of customary law communities and their rights as long as they are alive and in accordance with the development of society and the principles of the Republic of Indonesia. Based on this Law, the unitary state of the Republic of Indonesia recognizes and protects the existence of customary law communities, so with Law no. 6 of 2014 concerning villages and the decision of the Minister of Environment and Forestry of the Republic of Indonesia. That after there is a recognition from the Regent of Gunung Mas regarding the protection and recognition of Indigenous peoples, it is necessary to make regulations on the management of customary territories; The rules of Lewu Tehang customary rules so far have only been oral, so it needs to be made in writing, to be a guideline for the customary law community and other related parties; Customary territories need to be managed for the welfare of customary law communities, which are sustainable